Cost–utility analysis of nanoparticle albumin-bound paclitaxel versus paclitaxel in monotherapy in pretreated metastatic breast cancer in Spain. (June 2013) - Alba, Emilio; Ciruelos, Eva; López, Rafael; López-Vega, José Manuel; Lluch, Ana; Martín, Miguel; Muñoz, Montserrat; Sánchez-Rovira, Pedro; Seguí, Miguel Ángel; Liria, Marta Rubio; Pérez-Alcántara, Ferran
Aim: The COSTABRAX study evaluated the cost–effectiveness of nanoparticle albumin-bound paclitaxel (nab-paclitaxel) versus polyethylated castor oil-based standard paclitaxel (sb-paclitaxel) in the treatment of patients with previously treated metastatic breast cancer in Spain.Materials & methods: Efficacy data were obtained from the CA012 trial (nab-paclitaxel administered every 3 weeks [q3w] and sb-paclitaxel q3w) and indirect comparison (sb-paclitaxel administered weekly), and were modeled to a time horizon of 5 years using a Markov model. The analysis was performed from the National Health Service perspective. Use of resources and key assumptions of the model were validated by a panel of 22 local oncologists.Results: Compared with sb-paclitaxel q3w, nab-paclitaxel q3w was cost effective, with a cost per life year gained of €11, 088 and a cost per quality-adjusted life year of €17, 808. Compared with sb-paclitaxel administered weekly, it showed savings of €711 per patient.Conclusion: The COSTABRAX study showed that nab-paclitaxel q3w is a cost-effective alternative compared with sb-paclitaxel q3w and a cost-saving alternative to sb-paclitaxel administered weekly in Spain.